The Implementation of Character Education In Dayah Thalibul Huda of Aceh Besar - Saiful Saiful (Cendikia : Media Jurnal Ilmiah Pendidikan, 2022)
One of the hallmarks of education system in Dayah of Thalibul Huda of Aceh Besar is the student character building which can give birth to graduates having idealism, intellect, and good behavior (akhl?qal-kar?mah). This research aims to know the character education implementation in Dayah Thalibul Huda of Aceh Besar and to recognize the factor of success and inhibiting factor of character education in Dayah Thalibul Huda of Aceh Besar. Grand theory of this research employs theoretical framework proposed by Thomas Likcona consisting of moral knowing, moral feeling, and moral action. Furthermore, this research applies descriptive method with qualitative approach. Data collection techniques are observation, interview, and documentation. The result of this research shows that the implementation of character education in Dayah Thalibul Huda of Aceh Besar includes: (a) Moral knowing development, (b) Moral feeling development, (c) Moral action development. In addition,the character education factor of success comprises student’s obedience, the value and culture existence of Islamic school/dayah, teungku as student’s educator and counselor, school facilities, parents’ responsibility to improve student’s learning motivation and to strengthen human relationship. Besides, the inhibiting factors include student’s background, student’s different character, economic status and different culture and intellient level of the student.